Junior high drama. The middle school mean queens - Simonson, Louise (Stone Arch Books, 2019)
Lilly desperately wants to be one of the "cool girls" at Memorial Middle School, so she is thrilled to be invited to Tania's birthday party; but Tania is actually interested in Lilly's older brother, Hank, and when that does not work out she turns on Lilly, bullying her and making her life miserable--until a suggestion from her favorite teacher, and a campaign against bullying, provides Lilly with a connection to other victims in her school and an outlet for her emotions.